Improving Students’ Reading Comprehension Text through Concept-Oriented Reading Instruction (CORI) - Sugiarto, Dody; Indrawati, Indrawati; Meygita, Rica (English Education Department, 2021)
The aim of this research is to know the implementation of Concept-Oriented Reading Instruction (CORI) in improving students’ reading comprehension of analytical exposition text and to find out whether there is a significant difference between students who were taught by using CORI and those who were not. This research used quantitative approach with experimental research which was conducted at an Islamic High School in Kemuja, Bangka Belitung Province. The researcher used purposive sampling technique and two classes were taken as the sample. The result of the test was analyzed by using statistical analysis of paired sample t-test and independent sample t-test. The result showed that the students who learned by using CORI got higher score than those who did not. It could be seen from the result of independent sample t-test of students’ post-test between experimental group and control group, the t-obtained in equal variences assumed was 2.385, and the significant (2-tailed) was 0.023. Since t-obtained was higher than t-table (2.385 > 2.036) and the significant (2-tailed) was lower than computation with level significant (0.023 < 0.05). Based on the fact above, it could be concluded that CORI significantly improved the students’ reading comprehension.